Penguatan Sikap Peduli Lingkungan Peserta Didik melalui Pendekatan Jelajah Alam Sekitar (JAS) Berbasis Model Problem Base Learning (PBL) - Eriana Cahyaningtyas; Bayu Widiyanto; Mobinta Kusuma (Cakrawala: Jurnal Pendidikan, 2019)
This study aims to determine the effect of the “Jelajah Alam Sekitar”/ Approach of Natural Around (JAS) Based on the Problem Base Learning Model (PBL) Through Observation of Pollution Indicators Towards Learners' Environmental Care Attitudes. The data analysis of this study was divided into two, namely the initial data analysis in the form of a validity test using product moment correlation, reliability test and final data analysis in the form of a final data test covering descriptive analysis, normality test, homogeneity test, t test (paired sample t test) , descriptive attitude care about the environment. The results showed that the learning of science based on the JAS approach with the PBL method on environmental attitudes of students on the theme of pollution is influential because by using the t test (paired sample t test) the sig (2-tailed) value of 0,000 <0.05 was obtained. Learning by using a Natural Approach to explore around the PBL Model based can be applied in the eyes of natural science students, especially in environmental pollution material because according to this research Approach to the Natural Approach Around the PBL model based can improve students' environmental care attitudes